2019
DOI: 10.1088/1755-1315/341/1/012188
|View full text |Cite
|
Sign up to set email alerts
|

The use of single-nucleotide polymorphism in creating a crossline of meat simmentals

Abstract: The article presents the materials of the study on bull cross of the Bredy meat type simmentals, which include the genotyping of animals for the CAST and CAPN1 genes with the identification of frequencies of genotype and alleles, as well as testing the production of these animals expressed in the evaluation of aged within 8 days of meat for the indicators tenderness, juiciness, organoleptic assessment of taste. The results of the studies did not confirm, with certainty, the influence of the CAST gene polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…При этом организации полноценного кормления необходимо уделять постоянное внимание при всех формах ведения скотоводства. Уровень кормления и сбалансированность рационов по основным питательным веществам во многом способствуют проявлению генетического потенциала продуктивности, определяют тем самым энергию роста, живую массу и размеры животного, его экстерьер и убойные качества [7][8][9][10][11][12][13][14].…”
Section: разведение селекция генетикаunclassified
“…При этом организации полноценного кормления необходимо уделять постоянное внимание при всех формах ведения скотоводства. Уровень кормления и сбалансированность рационов по основным питательным веществам во многом способствуют проявлению генетического потенциала продуктивности, определяют тем самым энергию роста, живую массу и размеры животного, его экстерьер и убойные качества [7][8][9][10][11][12][13][14].…”
Section: разведение селекция генетикаunclassified
“…In the present study are found some SNPS with results an amino acids changes for the genes studied. Although theses modification could be associated to beef quality characteristics this results should not consider isolate because of according some studies have showing that occurrence of SNPs in different genes can be associated to same characteristic of meat quality in cattle (Bolormaa et al, 2011;Orrù et al, 2011;Tyulebaev et al, 2019).…”
mentioning
confidence: 92%
“…Molecular biology techniques have developed rapidly in recent years; they allow the determination of the frequencies and population genetic parameters of genes that are associated with economically relevant characteristics in cattle. In recent years, studies have shown that performance, fattening, carcass and meat quality traits in many cattle breeds are associated with polymorphisms and with genotypic and allelic frequencies of several genes (LEP, CAST, CAPN1, GHR, FABP4, DGAT1, CSN3, LGB, MYF5, TG, IGF1, IGF1R, LGB, ANK1 and OLR1) (Thaller et al, 2003;Curi et al, 2005;Borges et al, 2014;Ardicli et al, 2017;Ardicli et al, 2019a;Ardicli et al, 2019b;Carvalho et al, 2019;Tyulebaev et al, 2019). These traits related to beef quality are very important since they involve economic issues along the beef production chain (farm to fork).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of crossbreeding on meat production can only be seen if a full, balanced feed is provided to the crossbreds. This can be monitored by determining the balance of nutrients and minerals in the body of fattened young animals (Kosilov et al, 2006;Nikonova et al, 2014;Kosilov et al, 1997;Bozymov et al, 2016;Speshilova et al, 2014;Nagdalian et al, 2020;Vil'ver et al, 2017;Kosilov et al, 2017;Zadnepryanskii et al, 2012;Kayumov et al, 2019;Mironova et al, 2018;Fatkullin et al, 2018;Sedykh et al, 2018;Tyulebaev et al, 2019).…”
Section: Introductionmentioning
confidence: 99%